HUBUNGAN ANTARA OVERTHINKING DENGAN MINAT KARIER SISWA DALAM MEMILIH SEKOLAH LANJUTAN - Adelia, Patricia Vonny; Setiawan, Antonius Ian Bayu (Universitas Muria Kudus, 2025)
This study aims to: (1) to find out the relationship between overthinking and career interest in choosing a follow-up school for students in Bentara Wacana Muntilan Junior High School, (2) to find out the level of overhingking in choosing a follow-up school for students in Bentara Wacana Muntilan Junior High School, (3) to find out career interest in choosing a follow-up school for students in Bentara Wacana Muntilan Junior High School. This research method uses a quantitative descriptive correlation approach. The results showed that: (1) there is a negative relationship between overthinking and career interest with the acquisition of a correlation value (R) of -.389, (2) the level of overthinking in the low category with the acquisition of 87% and 78 students, (3) the level of career interest in the medium category with the acquisition of 40% and 36 students.